From experience to expectation: The reverse effect of power on purchasing impulsiveness - Wang, Yanzhi; Yao, Tang; Qiu, Qi (Frontiers in Psychology, 2023)
This research investigates how consumer purchasing impulsiveness can be influenced by their power experience and power expectation. The results show that powerful consumers are more likely to impulsively buy hedonic products; while powerless consumers prefer to impulsively buy utilitarian products (studies 1 and 2). However, when experiencing power expectation, powerless consumers feel a lower perception of deservingness, which reduces their impulse to buy hedonic products. In contrast, when powerful consumers imagine how powerful people should do in consumption, they will experience a higher sense of deservingness and increase purchasing impulsiveness for hedonic products, but their impulsiveness for purchasing utilitarian products is not affected (study 3). The underlying mechanism is that deservingness plays a mediation role in the impact of interactions between power perception and product attribute on purchasing impulsiveness when consumers feel the power expectation (study 4). Finally, theoretical contributions and managerial implications are discussed.